Pengaruh Model Pembelajaran Inkuiri Berbantuan Laboratorium Virtual Terhadap Penguasaan Konsep Fisika Peserta Didik - Mahesti Kusdiastuti; Ahmad Harjono; Hairunnisyah Sahidu; Gunawan Gunawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
This study aims to determine the effect model of inquiry aided virtual laboratory to physical concept comprehension of students MA DI Putri Nurul Hakim Kediri the academic year 2015/2016. Experimental research design using "pre-test-post-test control group design". The population in this study were all students of class X MA DI Putri Nurul Hakim Kediri totaling 5 classes, while samples were students of class X.1 as an eksperiment class majoring in X.2 as a control class. The data collection concept comprehension using techniques shaped test multiple choice. The research hypotheses were tested by t-test polled variance variance with significance level of 5% that is a hypothesis which does not indicate a specific direction. The results showed that physical concept comprehension ability of students learning with virtual media-aided model of inquiry higher than those not using the model inquiry-aided virtual laboratory.